EP397 Clinical contribution of antecedent ligation of uterine vessels in radical hysterectomy to the prognosis of patients with uterine cervical cancer. (1st November 2019) - Saito, F; Katabuchi, M; Takaishi, K; Motohara, T; Sakaguchi, I; Miyahara, Y; Honda, R; Tashiro, H; Ohba, T; Katabuchi, H
Abstract : Introduction/Background: In Japan, radical hysterectomy (RH) has been widely performed for patients with invasive uterine cervical cancer, resulting in favorable outcome. However, recurrence, which might have been induced by hematogenous metastasis, is defined as the development of distant metastasis in some cases. From 2006, we have performed RH with antecedent ligation of uterine vessels before pelvic lymphadenectomy t o prevent hematogenous metastasis. The objective of this study is to evaluate the clinical contribution of antecedent ligation of uterine vessels in RH to the prognosis of patients with uterine cervical cancer. Methodology: Two hundred fifty-five patients who underwent RH at Kumamoto University Hospital between 2000 and 2011 were identified. Retrospective analyses were performed between 2 groups according to the surgical approach. The patients who underwent RH with conventional surgical procedures before 2006 were assigned to conventional surgery group (n=98). Another group (antecedent ligation group) consisted of patients who underwent RH with a pelvic lymphadenectomy following antecedent ligation of uterine vessels after 2006 (n=157). The site of initial recurrence within 5 years and histological type were analyzed. Survival estimates used the Kaplan-Meier methods. Results: At a median follow-up of 88 months, 49 events had been observed and 31 patients had died. The 5-year overall survival rates were similar between groups (83.7% vs 90.4%, p=0.12). Among squamous cell carcinoma (SCC) patients, there were no differences in the 5-year overall survival rates and recurrences between groups. For non-SCC patients, RH with antecedent ligation of uterine vessels improved the 5-year overall survival rates (70.3% vs 88.0%, p=0.06). Furthermore, antecedent ligation of uterine vessels in RH was associated with a lower rate of extrapelvic recurrence than conventional surgery (21.6% vs 6.0%, p=0.03) in patients with non-SCC uterine cervical cancer. Conclusion: Antecedent ligation of uterine vessels in RH may improve the survival in patients with non-SCC uterine cervical cancer. Disclosure: Nothing to disclose.